Biofilm production by Staphylococcus aureus strains isolated from cystic fibrosin patients - Kukla, Rudolf; Paterová, Pavla; Mazurová, Jaroslava (University of Pardubice, 2012)
Cystic fibrosis is a serious genetic disorder affecting respiratory, gastrointestinal and genital tracts. The most common causes of health status deterioration of patients with cystic fibrosis are still considered to be bacterial infections. Staphylococcus aureus is one of the most common pathogens isolated from the air passages of these patients. The purpose of our study was to determine the ability and intensity of the biofilm production by 59 of Staphylococcus aureus strains isolated from the air passages of patients with cystic fibrosis in the Cystic fibrosis center at the University Hospital Hradec Kralové. We also evaluated biofilm production and its intensity in 59 Staphylococcus aureus strains isolated from the air passages of control group patients. The control group was formed by patients with nosocomial pneumonia hospitalized in the University Hospital. For assessing the biofilm production, we used modified microtiter-plate test by Christensen. We divided the intensity of biofilm production into four categories according to the measured optical density — negative, weak, medium and strong. Out of total 59 Staphylococcus aureus strains isolated from the air passages of cystic fibrosis patients 45 (77.2 %) strains produced biofilm in various degrees: 21 (35.6 %) weakly, 6 (10.2 %) medium and 18 (30.5 %) strongly. Similar results were determined for strains isolated from control group: 22 (37.3 %) weak, 13 (22.0 %) medium and 9 (15.3 %) strong biofilm producing strains. We found no statistically significant difference in the biofilm formation between both groups of Staphylococcus aureus strains.